The Main Problems and Typological Features of the Definition of the Concept of "Artistic Text" - Zakaryan, Hripsime (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
Definitions of the meaning of the concept of "text", its functions and characteristics are diverse and multifaceted, which is due to the direction in which the latter is being studied. Consequently, the multidisciplinary facets of his research require different approaches. In this article, a literary text is defined as a kind of communicative unit endowed with structural integrity, the most complex form of communication, carrying specific (emotional, logical, aesthetic, etc.) information, characterized by a special author’s style and worldview and ideological guidelines. The author of the text, the work and the reader are in direct contact, constantly interacting with each other. The purpose of the article is to determine the content of the concept of "text" and to identify its essential definitions. To achieve the stated goal, the following tasks were set: define the term "text" from the standpoint of various scientific approaches, with specific usage and meaning; highlight the relationship in the chain "author-work-reader"; characterize the concept of the author’s style and identify the role of the latter in creating the meaning of a literary text. The theoretical basis of the article was the scientific research of W. Eco, R. Barth, M. Bakhtin, G.-G. Gadamer and other scientists devoted to various principles of hermeneutics and interpretation of a literary text. The analytical method, methods of systematization and generalization are used as the main one in the article. The topic of the article is relevant, since the study of the problems of the concept of "text" and its features is one of the most common areas in modern science. This article is a definite scientific contribution within the framework of theoretical understanding and interpretation of a literary text.